Sistem Informasi Penilaian Kinerja Berbasis Web Pada PT. Bumi Sentosa - Ni Nyoman Emang Smrti; I Putu Gd Sukenada Andisana; Ibnu Atho'illah; I Gede Arya Purusa Dhana; I Gusti Ngurah Ary Widiatmika; Dadan Abdullah; Nuni Diyah Ansori; I Nyoman Trisna Wijaya Giri (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2022)
Human Resources in the company is a very valuable asset. Without employees the company will not run. In order to achieve the company's vision and mission, all important components of the company must be managed carefully. Good management of human resources and giving rewards to employees will increase enthusiasm for work so that the company will grow even better. Determination of rewards in the company requires a good record and a definite assessment pattern so as to produce accurate numbers so that justice can be felt by employees. In order to facilitate the calculation of rewards and documentation of calculation results, a web-based system was created to calculate the performance of human resources based on case studies at company PT. Bumi Sentosa specifically in the service department.